2019
DOI: 10.3390/molecules24173090
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Polysulfides, Polysulfanes, and Other Unique Species in the Reaction between GSNO and H2S

Abstract: Glutathione-based products, GSnX, of the reaction of hydrogen sulfide, H2S, S-nitroso glutathione, and GSNO, at varied stoichiometries have been analyzed by liquid chromatography high-resolution mass spectrometry (LC-HRMS) and chemical trapping experiments. A wide variety of glutathione-based species with catenated sulfur chains have been identified including sulfanes (GSSnG), sulfides (GSSnH), and sulfenic acids (GSnOH); sulfinic (GSnO2H) and sulfonic (GSnO3H) acids are also seen in reactions exposed to air. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In this manner, the possible reaction of NO with CSE-generated H 2 S is also prevented, thereby excluding the formation to any significant extent of hybrid H 2 S/NO species that could themselves react with CSE [ 26 ]. Under the tested conditions, given the reactants’ concentrations and ratios and the timescale of the experiments, the possible reaction of H 2 S with GSNO is also unlikely to interfere with the measurements [ 50 , 51 , 52 ]. GSNO 0.5 mM (or buffer in control samples) was added to the reaction mixture and incubated for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…In this manner, the possible reaction of NO with CSE-generated H 2 S is also prevented, thereby excluding the formation to any significant extent of hybrid H 2 S/NO species that could themselves react with CSE [ 26 ]. Under the tested conditions, given the reactants’ concentrations and ratios and the timescale of the experiments, the possible reaction of H 2 S with GSNO is also unlikely to interfere with the measurements [ 50 , 51 , 52 ]. GSNO 0.5 mM (or buffer in control samples) was added to the reaction mixture and incubated for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The shift of sulfur speciation with a concomitant reduction in mitochondrial respiration emphasizes the role of H 2 S oxidation in mitochondrial function under hypoxia. Oxidized S-species display higher reactivities than H 2 S, both as reductants [ 55 ] and sulfonylating agents [ 49 ]; thus, these species may be important intermediates in processes canonically attributed to H 2 S. Distinguishing which small molecules regulate vascular functions both intracellularly and extracellularly may help clarify the paradoxical effect of a small, simple molecule such as H 2 S having biological specificity and control.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have proposed that sulfhydration proceeds through the action of small oxoacids of sulfur (SOS) [ 45 ], simple metabolites of H 2 S such as sulfenic and sulfoxylic acids, HSOH and HOSOH, shown in Scheme 1 , analogous to cysteine sulfenic and sulfinic acids [ 46 , 47 ]. Initially, we found that species such as HSOH, HOSOH, and other S-catenated species including polysulfides and polysulfide oxides such as thiosulfenic acids were generated by the oxidation of H 2 S with a variety of different oxidants such as peroxides, metmyoglobin and nitroso-glutathione, all of which can be found endogenously in biological systems [ 48 , 49 ]. These species were observed trapped in situ using the nucleophilic dimedone, DH, and an electrophilic trap iodoacetamide IAM [ 50 ], and then analyzed by liquid chromatography separation and high-definition mass spectrometry, LC HD MS.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that GSNO serves as an intracellular storage for NO, which can be released by the reaction with GPX or thioredoxin reductase [59]. GSNO can also release stored NO upon reaction with H 2 S or HS - [135], and can also lead to formation of polysulfane species [136]. In addition, Berenyiova et al [137] proposed that sulfide reaction with GSNO may lead to HNO synthesis.…”
Section: No and H 2 S Interactionsmentioning
confidence: 99%